Por onde respira a fala : da palavra poética como criação do real - Marques, Carlos José Lontra (2011)
Two sections comprise this work, which seeks to question the poetic word as a way of creating the real. In the first section, entitled "Aproximações", a meditation on certain thematic groups is elaborated in dialog with multiple voices, according to the questioning of the theoretical approaches that guide the proposed discussion, with particular focus directed to concepts such as time, flux, song, experience. In the second section, entitled "Leituras", three levels of analysis are created from the previously developed meditation, regarding the works of Orides Fontela, Fima Hasse Paes Brandão and Cecília Meireles.